A study on maternal near miss cases in tertiary care center, Chandrapur, Maharashtra, India - Ganvir, Priti Pralhad; Thakare, Sarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Obstetrics near miss is an important indicator that reflects the quality of obstetrics care in a health facility. It assesses and monitors the activities aimed for prevention of maternal mortality. The aim and objective of this study was to find out the incidence, the prevalence and the causes of maternal near miss cases due to severe obstetrics complications. Methods: This is a retrospective study done in department of obstetrics and gynecology in GMC Chandrapur. The study was done during a period from 1st January 2019 to 31st December 2019. Results: In this study the hospital maternal near miss incidence ratio was 13.11%. In this study authors found the most common morbidity was (36.06%) hypertensive disorders of pregnancy, (28.68%) cases of major obstetric haemorrhage, (7.37%) severe systemic infection or sepsis, (2.45%) labour related disorders. In medical disorders very severe anaemia, (13.11%) was most common cause of near miss. The most common cause of death was post-partum haemorrhage (41.66%) and most of the patients referred from periphery in very critical condition. Conclusions: Haemorrhage and hypertension disorders are the leading causes of MNM. Prompt diagnosis and adequate management of near miss cases can reduce mortality rates.